2003
DOI: 10.1021/ja030299w
|View full text |Cite
|
Sign up to set email alerts
|

The Charge-Transfer Motif in Crystal Engineering. Self-Assembly of Acentric (Diamondoid) Networks from Halide Salts and Carbon Tetrabromide as Electron-Donor/Acceptor Synthons

Abstract: Unusual strength and directionality for the charge-transfer motif (established in solution) are shown to carry over into the solid state by the facile synthesis of a series of robust crystals of the [1:1] donor/acceptor complexes of carbon tetrabromide with the electron-rich halide anions (chloride, bromide, and iodide). X-ray crystallographic analyses identify the consistent formation of diamondoid networks, the dimensionality of which is dictated by the size of the tetraalkylammonium counterion. For the tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 61 publications
12
111
0
2
Order By: Relevance
“…Furthermore, solutions containing bromoform and either bromide or chloride as tetraalkylammonium salts showed no new bands at wavelengths higher than 250 nm; and the measurements in the far-ultraviolet spectral region (λ < 250 nm) were barred by strong component absorptions. We similarly carried out UV-Vis spectral measurements of intermolecular interactions of CBr 4 or CHBr 3 with various alkyl-substituted benzenes and polycyclic aromatics, as well as alkylamino-and methoxysubstituted benzenes containing both aromatic and heteroatom (n-donor) centers. However, only the addition of tetramethyl-p-phenylendiamine (TMPD) to the CBr 4 solution in dichloromethane led to the appearance of a clear (new) absorption band with maximum around 380 nm (which was not present in the spectrum of either the separate donor or acceptor).…”
Section: Electronic Spectra and The Thermodynamics Of Cbr 4 /Chbr 3 Bmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, solutions containing bromoform and either bromide or chloride as tetraalkylammonium salts showed no new bands at wavelengths higher than 250 nm; and the measurements in the far-ultraviolet spectral region (λ < 250 nm) were barred by strong component absorptions. We similarly carried out UV-Vis spectral measurements of intermolecular interactions of CBr 4 or CHBr 3 with various alkyl-substituted benzenes and polycyclic aromatics, as well as alkylamino-and methoxysubstituted benzenes containing both aromatic and heteroatom (n-donor) centers. However, only the addition of tetramethyl-p-phenylendiamine (TMPD) to the CBr 4 solution in dichloromethane led to the appearance of a clear (new) absorption band with maximum around 380 nm (which was not present in the spectrum of either the separate donor or acceptor).…”
Section: Electronic Spectra and The Thermodynamics Of Cbr 4 /Chbr 3 Bmentioning
confidence: 99%
“…3). Noticeably, this (trigonal) acceptor is crystallized in chiral space group ([P2 1 3])-in comparison with [cubic] acentric symmetry of the corresponding crystals with the tetragonal CBr 4 .…”
Section: Crystallization Of Cbr 4 and Chbr 3 Complexes And An Overviementioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17][18][19][20] Concurrently, halide complexes of d-metals can be employed as XB acceptors and their combination with halomethanes leads to supramolecular clusters, chains, and 3D networks. 17,18,[20][21][22] The halomethanes CBr 4 , [11][12][13][18][19][20] CHI 3 , 14,15,17,23 CHBr 3 , 11,12,20 and CFBr 3 12,19 are the most commonly used among other halomethanes in the formation of XBs with uncomplexed halides and polyhalometalate anions. Our recent works indicated that even weak XB donors such as CHCl 3 , CH 2 Cl 2 , and CH 2 Br 2 ( Fig.…”
Section: Introductionmentioning
confidence: 99%